Developing application software to quickly detect the adolescent’s risky behaviour to prevent teen pregnancy - Deswinda; Dini Maulinda; Iyang Maisi Fitriani (Journal of the Pakistan Medical Association, 2024)
Objective: To develop a software application for early detection of adolescent’s risky behaviour, and promotion of safe reproductive health. Method: The multi-stage study was conducted from September 20, 2018, to April 3, 2019, at Rumbai District Pekanbaru, Riau-Indonesia. The planned software application was developed using the waterfall design model which is a sequential process. Every progress was acknowledged to be flowing downwards, like a waterfall, by going through the phases of requirements, design, implementation, verification and maintenance. The application software was pilot-tested on a group of adolescents after it was first tested for validity. The adolescents were given a questionnaire at baseline and 2 weeks after the intervention to assess the application’s effectiveness. The data was analyzed using SPSS version 21. Results:Validation of the tool was confirmed by Aiken’s V values >0.85, with sensitivity 84.8% and specificity 75%. Of the 45 adolescents tested, majority respondens were girls 38(84,4%), early adolescent 18(40%), middle adolescent 16(35,5%) and late adolescent 11(24,4%). About 5(11.1%) were found to be positive, and 28(62.2%)were truly positive, while 3(6.7%) were found negative and 9(20%) were truly negative. There was a significant difference between the pre-test and post-test assessments (p=0.0001). Conclusion:The application proved to be effective for the early detection of risky behaviour, and for the promotion of safe reproductive health. Keywords: Adolescent, Reproductive Health, hapus Knowledge, Attitudes, Practice